Conventional and dual competitive binding analyses of thyroxine using the Thyopac-4 kit. Issue 5 (May 1974) - Hamada, Satoshi; Torizuka, Kanji; Uete, Tetsuo
Abstract : A simple method is described for the simultaneous determinations of thyroxine and the effective thyroxine ratio (ETR) using a single kit of Thyopac-4. Thyopac ETR values obtained were 1·00 ± 0·03 for normal subjects; 1·22 ± 0·11 for hyperthyroid; 0·87 ± 0·04 for hypothyroid; and 1·02 ± 0·05 for pregnant women. Cases with TBG deficiency and the nephrotic syndrome indicated normal values. The value ( x ) was correlated significantly (γ = + 0·961) with the free Thyopac index ( y ), representing a regression equation of y = 71·7 x 2 − 88·4 x + 24·2. Thyopac ETR was shown to be useful in differentiating normal thyroid states from abnormal, irrespective of changes in T4 -binding globulin (TBG). Further, the T4 value obtained simultaneously made it possible to detect changes in the TBG level by noting an inconsistent value for the effective thyroxine ratio.